Employer branding: Confirmation of a measurement model and its implication for managing the workforce. (January 2023) - Sarabdeen, Jawahitha; Balasubramanian, Sreejith; Lindsay, Valerie; Chanchaichujit, Janya; Sreejith, Sony
Employer branding is becoming increasingly important for organizations to attract and retain top talent. While practitioners use a range of tactics to build and promote employer branding, it is still unclear as to what exactly constitutes effective employer branding. This gap in the literature formed the motivation of this study, which aims to develop, validate and apply a multi-dimensional measurement model of employer branding. First, a comprehensive measurement model of employer branding comprising eight constructs (brand value, development value, economic value, ethical and moral value, functional value, interest value, management value, and work-life balance) was developed through an extensive literature review. Next, using data collected through a structured survey, the validity of the proposed model, including the relevance/appropriateness of each construct and its unique contribution to employer branding, was assessed. The second-order confirmatory factor analysis results established the existence of a robust higher-order measurement model for employer branding, with each of the eight constructs contributing significantly and uniquely. The model was then applied to assess the hypothesized difference in employer branding across different demographic groups, namely gender and overall work experience. The results indicate a significant difference in the model across the various demographic groups. Overall, the study significantly contributes toward the theoretical advancement of employer branding. Future researchers could adopt the validated model and measurement items in different settings. For practitioners, the results indicate that employer branding requires an all-encompassing effort rather than being oriented towards few attributes. Also, the study findings highlight the need to customize employer brand strategies across different demographic groups.